Qualitative and quantitative analysis of colorimetric response in different UV solar radiation level indicator bracelets based on photochromic substances - Aguilera, J.; Cárdenas-González, D.; Sánchez-Roldán, C.; González, S.; Bosch-García, R.; Herrera-Ceballos, E.; de Gálvez, M. V. (Frontiers in Photobiology, 2024)
Background and Objective We are exposed to solar radiation from early childhood, so learning different photoprotection strategies is fundamental. As a primary prevention tool, knowledge of the solar ultraviolet radiation to which we are exposed is fundamental. There are devices based on the color change of photochromic substances when exposed to UV radiation which are widely used as a tool for children’s play. The aim was to assess both quantitatively and qualitatively the effectiveness of the use of these devices under different conditions of simulated sun exposure. Materials and Methods Ten commercial UV-indicating photochromic devices plus three pure photochromic substances were used. Photochromic devices belong to the spirooxazine family of molecules. They were exposed to different rates of UV radiation under a solar UV-visible simulator, and their velocity, degree of response, and color reversal time were analyzed both visually and objectively using a colorimeter based on three-dimensional CIE L*a*b* color space values. Activation response was also evaluated under different UV high-energy visible light wavelengths using different cut-off filters. Finally, the devices were exposed under high UV irradiance (corresponding to UVI of 10) and interposing sunscreens of different sun protection factors in order to evaluate their potentials as indicators for sunscreen re-application. Results All the devices and pure substances offered color change almost immediately under simulated solar radiation. From very low irradiances (UVI >3), they saturated color, and it was not possible to observe and measure color change. The time to color reversal took longer than activation (from 60 s to obtain initial values). When devices were exposed to a UVI of 10 with topical sunscreen overlay, color was observed after 1 min irradiation even under SPF of 50+ sunscreen. Photochromic devices were activated under both UVA and high energy visible light. Conclusion UV radiation indicators using photochromic substances which, although possible awareness-raising elements, are of limited use as indicators of UV radiation intensity and dosimetry. They are useful elements for detecting the presence/absence of UV radiation and do not distinguish between different UV radiation spectral bands. Moreover, their incorporation as photoprotective elements used by minors could lead to exposures that are not objectively controlled.